2021
DOI: 10.1007/s00414-021-02606-y
|View full text |Cite
|
Sign up to set email alerts
|

Myelin basic protein and neurofilament H in postmortem cerebrospinal fluid as surrogate markers of fatal traumatic brain injury

Abstract: The aim of this study was to investigate if the biomarkers myelin basic protein (MBP) and neurofilament-H (NF-H) yielded informative value in forensic diagnostics when examining cadaveric cerebrospinal fluid (CSF) biochemically via an enzyme-linked immunosorbent assay (ELISA) and comparing the corresponding brain tissue in fatal traumatic brain injury (TBI) autopsy cases by immunocytochemistry versus immunohistochemistry. In 21 trauma and 19 control cases, CSF was collected semi-sterile after suboccipital punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In this study, we also found upregulation of Myelin Basic Protein (MBP) and associated proteins in the brain following stress in accordance with previous studies. MBP has been associated with neuronal death and trauma and has been found to be increased in CSF of dogs post traumatic brain injury (Bohnert et al , 2021; Su et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found upregulation of Myelin Basic Protein (MBP) and associated proteins in the brain following stress in accordance with previous studies. MBP has been associated with neuronal death and trauma and has been found to be increased in CSF of dogs post traumatic brain injury (Bohnert et al , 2021; Su et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CSF samples were immediately centrifuged at 5000 rpm for 5 min at 4 °C and cytospin preparations were stained with the antibody mentioned above using an adapted protocol for immunocytochemistry [ 13 ] and identical dilutions .…”
Section: Methodsmentioning
confidence: 99%
“…Since the CSF is permanently resorbed, interstitial fluid (ISF) influx carrying degenerated proteins and waste products from all parts of the central nervous system (CNS) replenish resorbed CSF [3]. Cellular, microbial, metabolic, and structural proteins are considered as biomarkers that act as surrogate markers of CNS neuropathology, e.g., after traumatization [4][5][6][7][8][9][10][11][12][13][14][15]. Research and diagnosis of enhanced CSF-cell density after inflammatory and tumor-related brain affliction have a long history [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When myelin fracture and disintegration occur in the central nervous system because of direct mechanical damage (namely primary brain injury, such as cerebral contusion or intracranial hematoma, or as the result of a brain tumor), the myelin component MBP is released into bodily fluids, thus causing secondary brain injury. 13 Studies have shown that serum MBP is a prognostic marker of brain injury. 14 Additionally, changes in blood MBP levels may reflect the degree of glial injury in the central nervous system; however, few clinical studies have investigated whether changes in MBP may be an index for the development of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%